Traditional rating of noise versus physiological costs of sound exposures to the hearing - Strasser, Helmut (Biomedical and health research ;, 2005)
In occupational safety and health acts, ordinances, regulations, directives, standards and guidelines, A-weighted sound exposures, varying in level and duration, are traditionally converted to an 8-hour-average sound level by applying the 3-dB exchange rate. Under the prerequisite that the energy equivalent rating level does not exceed 85 dB(A)/8 h, even impulse noise exposures of up to 140 dB are declared harmless. Indeed, the mutual settlement of level and duration based on the concept of energy equivalence is correct as far as sound energy or physical dose is concerned. However, between thi.